Efficiency Marketing Analysis of Smallholder Beef Cattle Business in Angkola Sangkunur Subdistrict South Tapanuli Regency - R.A.S. Harahap; G.A.W. Siregar; N. br Ketaren; K. Daulay (Talenta Publisher, 2025)
Cattle farming practices in South Tapanuli Regency are still carried out traditionally wich cause less margin. This study aims to determine the characteristics of marketing institutions involved in marketing, marketing channels, and marketing efficiency. This study uses the snowball sampling method. The respondents in this study were 37 farmers, 14 retailers, and 9 collectors. This research was conducted in South Tapanuli Regency, North Sumatra Province, specifically in Angkola Sangkunur Subdistrict in 3 villages, namely Sangkunur, Malombu, and Batu Godang, and there were 3 marketing channels. The research method used was quantitative with a survey type of research, namely by conducting direct observations in the field using interviews and questionnaires. The results of the study show that the marketing margin in channel II is IDR. 650,600/head. The marketing margin in channel III is IDR. 389,436/head. Farmer share in channel II is 103%, and in channel III is 102%. The profit-to-marketing cost ratio for channel II is 2.05, and for channel III it is 7.62. Marketing efficiency for channel II is 0.022, and for channel III it is 0.004. Beef cattle marketing in Angkola Sangkunur Subdistrict is considered efficient.